2017
DOI: 10.1002/jcb.25964
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow‐Derived Mesenchymal Stem Cells‐Mediated Protection Against Organ Dysfunction in Disseminated Intravascular Coagulation Is Associated With Peripheral Immune Responses

Abstract: Disseminated intravascular coagulation (DIC) is a fatal thrombohemorrhagic disorder. Bone marrow-derived mesenchymal stem cells (BMSCs) are multipotent stem cells that have tremendous therapeutic effect. Our aim was to explore whether the immune mechanisms were associated with BMSCs-afforded protection against DIC. We generated a rat model of DIC by lipopolysaccharide (LPS, 3 mg/kg) injection via the tail vein. In the treatment group, rats were pre-treated with 1 × l0 , 1 × l0 , 1 × l0 , and 1 × l0 allogeneic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…It has also been seen that pretreatment with BMSCs can alleviate coagulation and organ dysfunction in LPS-induced DIC rat models by regulating the immune cells and pro-inflammatory cytokines. 39,40 Previous studies focusing on plasma coagulation indicated the pro-coagulant and anti-coagulant activity of BMSCs. This study showed that BMSCs are dependent on their tissue of origin and inhibit platelet activation with the help of formation of adenosine from adenosine monophosphate due to the ecto-5ʹ-nucleotidase activity of CD73.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been seen that pretreatment with BMSCs can alleviate coagulation and organ dysfunction in LPS-induced DIC rat models by regulating the immune cells and pro-inflammatory cytokines. 39,40 Previous studies focusing on plasma coagulation indicated the pro-coagulant and anti-coagulant activity of BMSCs. This study showed that BMSCs are dependent on their tissue of origin and inhibit platelet activation with the help of formation of adenosine from adenosine monophosphate due to the ecto-5ʹ-nucleotidase activity of CD73.…”
Section: Discussionmentioning
confidence: 99%
“…The establishment DIC rat model was performed according to the methods described by our previous studies 23 , 26 . Rats were anesthetized with an intraperitoneal injection of pentobarbital sodium salt (30 mg/kg, Sigma-Aldrich).…”
Section: Methodsmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) can undergo self-renewal and differentiation into various cell types and tissues including chondrocytes, osteoblasts, and adipocytes [ 12 ]. Many studies have demonstrated that MSCs can suppress the activation and function of innate and adaptive immune cells, including macrophages [ 13 ], neutrophils [ 14 ], natural killer cells [ 15 ], dendritic cells [ 16 ], and T cells [ 17 ]. Many preclinical studies have demonstrated that treatment with MSCs can improve survival, reduce inflammation, and enhance bacterial clearance [ 18 21 ].…”
Section: Introductionmentioning
confidence: 99%